Pengaruh Pengendalian Intern, Kepatuhan Dan Integritas Manajemen Terhadap Perilaku Etis Karyawan Dalam Sistem Penggajian (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2021)
This research is to find out the Internal control, Compliance, and the Integritymanagement against of the ethical behaviour in payroll system both simultaneously or bepartial. The independent variable used in this research are internal control, adherence, andintegrity managment. While for dependent variable for ethical behaviour in payroll system.The method used in this research are using a technique descriptive analysis andverifikatif. A sample in this experiment to 59 people using simple random samplingtechniques. Technical data is a questionnaire. An instrument to test the validity of the data,test and test reliabilitas normality data analysis of the data is the correlation, determianasi,test hypotheses partial or be partial. Data processing using Statistical Product And ServiceSolution (SPSS ) versions 21 and Microsoft Excel in 2007.The results of these studies show that a partial variable internal control and integritymanagement have significant influence on Ethical Behaviour in Payroll System, and variablecompliance not have significant influence on Ethical Behaviour in Payroll System.Simultaneously variable internal control, compliance, and integrity management have asignificant positive against of the ethical behaviour in payroll system.